1997
DOI: 10.1074/jbc.272.13.8791
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Tectorins

Abstract: The cDNA and derived amino acid sequences for the two major non-collagenous proteins of the mouse tectorial membrane, ␣-and ␤-tectorin, are presented. The cDNA for ␣-tectorin predicts a protein of 239,034 Da with 33 potential N-glycosylation sites, and that of ␤-tectorin a smaller protein of 36,074 Da with 4 consensus N-glycosylation sites. Southern and Northern blot analysis indicate ␣-and ␤-tectorin are single copy genes only expressed in the inner ear, and in situ hybridization shows they are expressed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(64 citation statements)
references
References 55 publications
1
62
0
1
Order By: Relevance
“…The zona domain has been implicated in forming protein polymers not only in the zona pellucida matrix, but between constituents of the extracellular tectorin membrane found in the inner ear (10,47). Genetically altered mice lacking ZP1 form a zona matrix composed of ZP2 and ZP3 (48); mice lacking ZP2 form a thinner, more fragile matrix composed of ZP1 and ZP3 (49); but mice lacking ZP3 do not form a zona pellucida (11,50).…”
Section: Discussionmentioning
confidence: 99%
“…The zona domain has been implicated in forming protein polymers not only in the zona pellucida matrix, but between constituents of the extracellular tectorin membrane found in the inner ear (10,47). Genetically altered mice lacking ZP1 form a zona matrix composed of ZP2 and ZP3 (48); mice lacking ZP2 form a thinner, more fragile matrix composed of ZP1 and ZP3 (49); but mice lacking ZP3 do not form a zona pellucida (11,50).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above, the TM is likely to play an important role in delivering sound-induced mechanical stimuli to OHC hair bundles, as well as in communicating between OHC and IHC hair bundles. Further support for the important role of the TM in hearing is obtained from recent studies, which have shown that mutations in proteins of the TM cause auditory impairments (5)(6)(7)(8).…”
mentioning
confidence: 95%
“…Mutations in ZPDs, especially in the NTS, can result in severe pathologies, such as infertility, deafness, and cancer. In this context, it was proposed that ZPDs might play a role in polymerization of proteins into fibrils or matrices (25). Indeed, it was found that ZPDs polymerize into fibrils on their own (26) and that the NTS is responsible for polymerization (27).…”
Section: Structural Features Of Zpgsmentioning
confidence: 99%